Complications after emergency laparotomy beyond the immediate postoperative period – a retrospective, observational cohort study of 1139 patients2. (3rd November 2016) - Tengberg, L. T.; Cihoric, M.; Foss, N. B.; Bay‐Nielsen, M.; Gögenur, I.; Henriksen, R.; Jensen, T. K.; Tolstrup, M.‐B.; Nielsen, L. B. J.
Summary: Mortality and morbidity occur commonly following emergency laparotomy, and incur a considerable clinical and financial healthcare burden. Limited data have been published describing the postoperative course and temporal pattern of complications after emergency laparotomy. We undertook a retrospective, observational, multicentre study of complications in 1139 patients after emergency laparotomy. A major complication occurred in 537/1139 (47%) of all patients within 30 days of surgery. Unadjusted 30‐day mortality was 20.2% and 1‐year mortality was 34%. One hundred and thirty‐seven of 230 (60%) deaths occurred between 72 h and 30 days after surgery; all of these patients had complications, indicating that there is a prolonged period with a high frequency of complications and mortality after emergency laparotomy. We conclude that peri‐operative, enhanced recovery care bundles for preventing complications should extend their focus on continuous complication detection and rescue beyond the first few postoperative days.